Healthy Nordic Diet Modulates the Expression of Genes Related to Mitochondrial Function and Immune Response in Peripheral Blood Mononuclear Cells from Subjects with Metabolic Syndrome–A SYSDIET Sub‐Study. Issue 13 (18th April 2019) - Myhrstad, Mari C. W.; de Mello, Vanessa D.; Dahlman, Ingrid; Kolehmainen, Marjukka; Paananen, Jussi; Rundblad, Amanda; Carlberg, Carsten; Olstad, Ole Kristoffer; Pihlajamäki, Jussi; Holven, Kirsten B.; Hermansen, Kjeld; Dragsted, Lars O.; et al.
Abstract : Scope: To explore the effect of a healthy Nordic diet on the global transcriptome profile in peripheral blood mononuclear cells (PBMCs) of subjects with metabolic syndrome. Methods and results: Subjects with metabolic syndrome undergo a 18/24 week randomized intervention study comparing an isocaloric healthy Nordic diet with an average habitual Nordic diet served as control (SYSDIET study). Altogether, 68 participants are included. PBMCs are obtained before and after intervention and total RNA is subjected to global transcriptome analysis. 1302 probe sets are differentially expressed between the diet groups ( p ‐value < 0.05). Twenty‐five of these are significantly regulated (FDR q ‐value < 0.25) and are mainly involved in mitochondrial function, cell growth, and cell adhesion. The list of 1302 regulated probe sets is subjected to functional analyses. Pathways and processes involved in the mitochondrial electron transport chain, immune response, and cell cycle are downregulated in the healthy Nordic diet group. In addition, gene transcripts with common motifs for 42 transcription factors, including NFR1, NFR2, and NF‐κB, are downregulated in the healthy Nordic diet group. Conclusion: These results suggest that benefits of a healthy diet may be mediated by improved mitochondrial function and reduced inflammation. Abstract : The intake of a healthy Nordic diet (ND) is compared with an average habitual nordic diet (CD) in subjects with metabolic syndrome (MetS) in this multicenter randomized intervention study. Total RNA is isolated from peripheral blood mononuclear cells (PBMCs) and subjected to microarray analysis.